Characterization, isotherm and kinetic study of Phaseolus vulgaris husk as an innovative adsorbent for Cr(VI) removal - Srivastava S.; Agrawal S.B.; Mondal M.K. (My University, 2025)
Phaseolus vulgaris husk as a novel, very common milling agro waste, showed good performance for mutagenic Cr(VI) removal from chromium enriched aqueous solution. The study involves batch experiments to investigate the effects of influencing parameters, such as pH, temperature, contact time, initial Cr(VI) concentration, and adsorbent dose, on the adsorption process. Results showed a maximum of 99.88% removal of Cr(VI) at pH 1.16, temperature 20 °C and adsorbent dose of 6 g L−1. The adsorption equilibrium data followed the Freundlich model, suggesting a heterogeneous nature of the adsorbent surface and the correlation coefficient for pseudo-second-order kinetic model was found to be very high, showing its applicability during the adsorption process. The maximum Cr(VI) uptake capacity was 3.4317mg g−1. Thermodynamic parameters like standard free energy change (−7.175 kJ mol−1), enthalpy change (−8.29 kJ mol−1) and entropy change (0.005 kJ mol−1 K−1) revealed the spontaneous and exothermic nature of adsorption of Cr(VI) onto P. vulgaris husk. Desorption with 1mol L−1 NaOH followed by 1mol L−1 HCl was effective (92.76%) and, hence, it exhibited the possibility of recycling of used husk. © 2016, Korean Institute of Chemical Engineers, Seoul, Korea.